2007
DOI: 10.1002/jnr.21307
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen is a preferred glutamate precursor during learning in 1‐day‐old chick: Biochemical and behavioral evidence

Abstract: Bead discrimination training in chicks sets in motion a tightly timed series of biochemical events, including glutamate release, increase in forebrain level of glutamate and utilization of glycogen and glucose. Inhibition of glycogen breakdown by the glycogen phosphorylase inhibitor 1,4-dideoxy-1,4-imino-D-arabinitol (DAB) around the time of training abolishes the increase in glutamate 5 min posttraining in the left hemisphere, in spite of uninhibited glucose metabolism. It also reduces the contents of glutama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
108
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 32 publications
9
108
0
Order By: Relevance
“…This supports the idea that glycolysis and glycogenolysis are compartmentalized in astrocytes (Sickmann et al, 2005;Gibbs et al, 2007).…”
Section: Interactions Between B 2 -And B 3 -Ars and Glucose Metabolismsupporting
confidence: 87%
“…This supports the idea that glycolysis and glycogenolysis are compartmentalized in astrocytes (Sickmann et al, 2005;Gibbs et al, 2007).…”
Section: Interactions Between B 2 -And B 3 -Ars and Glucose Metabolismsupporting
confidence: 87%
“…It should be noted, however, that although glycogen is confined to astrocytes, 39 it is also able to sustain energy homeostasis in neurons via conversion to lactate and transfer to the neuronal compartment for reconversion to pyruvate entering the TCA cycle for energy production. In addition, it has been demonstrated that glycogen is an important precursor for de novo synthesis of glutamate and glutamine, 40 i.e., for maintenance of cerebral amino-acid homeostasis. Accordingly, glycogen may be important as an energy substrate and/or as a precursor for amino-acid biosynthesis during seizure activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought of as an emergency fuel store during physiological and pathological stress such as hypoglycaemia or cerebral ischemia [6,7]. However, additional roles have been ascribed to glycogen: It can provide energy for rapid clearance by astrocytes of the neurotransmitter glutamate [8], serve as precursor of the carbon skeleton of glutamate [9], and provide NADPH for the disposal of peroxides in astroglial cultures [10]. In fact, the role of glycogen as an important component of normal brain metabolism is now under discussion [11].…”
Section: Introductionmentioning
confidence: 99%